Módulo antropología cultural. - Flores Bonilla, Luis Germán (1998)
Introduction. Anthropology as a science. Specializations. The fieldwork in anthropology. Major anthropological currents. The emergence of culture. Communication codes of culture. Language, Speech and dialect. Art as a form of communication. Linguistic diversity and political diversity. Identity and cultural change. Kinship systems. Economic organization. Political Organization. Indian nationalities. Reivindicaicón and political processes. Political process and self-definition as nationalities. Worldview and religion. Andean and Amazonian symbolic manifestations.